Optical spectroscopy study of hydrogenation of the Si(111)-7 × 7 surface - Roy, M.; Beitia, C.; Borensztein, Y.; Shkrebtii, A.; Noguez, C.; Del Sole, R. (Applied surface science, 1996)
Deposition of foreign atoms on silicon surfaces gives rise to a variety of phenomena, which are the subject of very active research. Fundamentally and technologically important, the chemisorption of hydrogen at Si(111)-7 × 7 surface is still under debate due to its complex structure, the existence of different adsorption sites and the etching in the process of adsorption. We present both experimental and theoretical optical spectroscopy results on the atomic hydrogen adsorption at the Si(111)-7 × 7 surface. The real-time optical, namely differential reflectivity, measurements were performed by means of an in-situ spectrometer with 60° angle of incidence. Structural changes upon H adsorption have been monitored by LEED. Microscopical calculation of the optical properties of the full scale Si(111)-7 × 7 DAS structure was done within a sp 3s ∗ tight-binding approach. In order to model the structural changes due to H adsorption, we calculated the relative difference in reflectivity ΔR R between the clean Si(111)-7 × 7 and hydrogenated Si(111)-1 × 1:H surfaces. The surface optical response has been decomposed into the various components, due to surface-to-surface, surface-to-bulk, bulk-to-surface and bulk-to-bulk states transitions. The microscopic origin of the different contributions is discussed in detail. The comparison with the theoretical results allowed us to clarify the origin of the main optical peaks observed experimentally at the hydrogenated Si(111)-7 × 7 surface.